Quartz fiber with yttrium oxide coating and preparation method thereof
By covering the yttrium oxide coating on the surface of the quartz fiber, the problem of the decrease in strength of quartz fiber under high temperature conditions is solved, and the effect of improving the high temperature and mechanical properties of quartz fiber is achieved.
Patent Information
- Application Number
- CN202411785601.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-14
AI Technical Summary
Quartz fiber has significantly reduced its strength under high temperature conditions, limiting its application in the field of high temperature wave transmission.
The yttrium oxide coating is covered on the surface of the quartz fiber, and a dense yttrium oxide coating is formed by the impregnation, drying and sintering process of the yttrium oxide sol.
It significantly improves the high-temperature sintering and mechanical properties of quartz fibers. The yttrium oxide coating has strong oxidation and ablation resistance under high temperature conditions, and protects the surface of quartz fibers.
Smart Images

Figure CN119430689A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high temperature resistant, oxidation resistant and wave-transmitting ceramics, and more specifically, relates to a quartz fiber with an yttrium oxide coating and a preparation method thereof. Background Art
[0002] With the rapid development of modern warfare, aerospace vehicles such as missiles will develop in the direction of high speed, long distance, high precision guidance, high maneuverability, etc. The radome / antenna window at the front end of the missile will face harsh extreme environments such as high temperature and high pressure, vibration impact, rain erosion and scouring. In order to ensure that the electromagnetic signal inside the radome / window can be transmitted normally, the corresponding preparation materials usually need to have excellent performances of wave transmission, load bearing and heat protection. How to prepare high-performance wave-transmitting materials is a technical problem that needs to be urgently solved in the production of supporting products such as radomes / windows in the future. Quartz fiber is the most commercialized and produced continuous fiber reinforcement at present. The quartz fiber reinforced ceramic matrix composite material prepared by it has excellent mechanical and thermal comprehensive performance and is widely used in the field of high-temperature wave-transmitting materials. However, studies have shown that when quartz fiber is treated at high temperature in air, its strength will decrease significantly, which limits its application as a fiber reinforcement in the field of high-temperature wave transmission. Therefore, introducing a high-temperature resistant anti-oxidation coating on the surface of quartz fiber to reduce the thermal damage of quartz fiber under high temperature conditions is an effective way to solve the temperature resistance of quartz fiber.
[0003] Corresponding improvements have also been made to address the above problems, such as China's patent application number CN201110122113.5, published on November 23, 2011. The patent discloses a method for surface modification of quartz fiber, which belongs to the technical field of quartz fiber composite materials, and includes the following steps: preparation of monodispersed SiO2 beads with a particle size of 100-600nm; surface treatment of quartz fiber by ablation and immersion, immersing the surface-treated quartz fiber in a sol to coat the surface of the quartz fiber with a layer of positively charged metal oxide film; immersing the positively charged quartz fiber in a suspension of silica colloidal particles to obtain a product. The disadvantage of this patent is that although the mechanical properties of the quartz fiber composite material at high temperature are effectively improved, new metal impurities are easily introduced, thereby affecting the dielectric properties of the quartz fiber.
[0004] Another example is Chinese patent application number CN202410959961.9, which was published on November 8, 2024. The patent discloses a method for preparing modified quartz fiber and its application in composite materials. The method is to repeatedly reflux-clean-dry the quartz fiber cloth with acetone to remove the surface impregnation agent of the quartz fiber; place the cleaned quartz fiber in dilute nitric acid to react and hydroxylate the quartz fiber; place the hydroxylated quartz fiber in tetrahydrofuran, add hydrogen-containing silane and catalyst to heat and react, and then slowly drip dilute hydrochloric acid solution into the reaction system. After the reaction, wash and dry to obtain modified quartz fiber; and prepare modified quartz fiber / silicone resin composite material by vacuum molding by compounding modified quartz fiber with hydroxy silicone resin. The disadvantage of this patent is that the entire preparation process is cumbersome, time-consuming, and inefficient. Summary of the invention
[0005] 1. Problems to be solved
[0006] In view of the problem that the performance of existing quartz fibers decreases at high temperatures, the present invention provides a quartz fiber with an yttrium oxide coating and a preparation method thereof. The present invention can greatly improve the high-temperature sintering performance of the quartz fiber by covering the surface of the quartz fiber with an yttrium oxide coating; the preparation process of the yttrium oxide sol is simple and low in cost; the prepared yttrium oxide sol has good stability and is better attached to the surface of the quartz fiber, thereby improving the impregnation effect.
[0007] 2. Technical solution
[0008] To solve the above problems, the present invention adopts the following technical solutions.
[0009] A method for preparing a quartz fiber with an yttrium oxide coating comprises impregnating the quartz fiber with an yttrium oxide sol, and drying and sintering the impregnated quartz fiber to obtain a quartz fiber with an yttrium oxide coating on the surface; the preparation process of the yttrium oxide sol is as follows:
[0010] S1: Add a ligand and a stabilizer to an yttrium nitrate solution in sequence, stir and dissolve to form a mixed solution, add a pH adjuster to adjust the pH value of the mixed solution to 7-8, heat to a target temperature, and then cool to obtain an yttrium oxide sol.
[0011] Furthermore, in step S1, the complexing agent is citric acid monohydrate, the stabilizer is one of polyethylene glycol-400, urea or triethanolamine, and the pH regulator is ammonia water.
[0012] Furthermore, the molar ratio of yttrium nitrate to citric acid monohydrate is 1:(1.0-2.0); the mass ratio of yttrium nitrate to stabilizer is (100-300):1.
[0013] Furthermore, in step S1, the target temperature is 50°C to 90°C, and the heating time is 30min to 90min.
[0014] Furthermore, in step S1, the yttrium nitrate solution is prepared by dissolving yttrium nitrate hexahydrate in water, and the concentration of the yttrium nitrate solution is 1.5 mol / L to 2.5 mol / L.
[0015] Furthermore, before the quartz fiber is impregnated with the yttrium oxide sol, the method further includes removing the organic impregnant on the surface of the quartz fiber.
[0016] Furthermore, the specific method for removing the organic impregnant on the surface of the quartz fiber is: the quartz fiber is subjected to heat sintering treatment in air to remove the organic impregnant on the surface, the sintering temperature is 400°C to 600°C, the heating rate is 5°C / min to 20°C / min, and the insulation time is 60min to 240min.
[0017] Furthermore, the quartz fiber is impregnated with the yttrium oxide sol for 30 minutes to 360 minutes, and the drying temperature is room temperature to 150°C.
[0018] Furthermore, the sintering temperature of the quartz fiber after impregnation is 200°C to 800°C, the heating rate is 5°C / min to 20°C / min, and the insulation time is 30min to 240min.
[0019] A quartz fiber with an yttrium oxide coating is prepared by using any of the above-mentioned methods for preparing a quartz fiber with an yttrium oxide coating.
[0020] 3. Beneficial effects
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The present invention can significantly improve the high-temperature sintering performance of quartz fiber by covering the surface of quartz fiber with yttrium oxide coating. At the same time, the yttrium oxide coating has strong oxidizability and ablation resistance under high temperature conditions, and protects the surface of quartz fiber, thereby improving the mechanical properties of quartz fiber at high temperature. In addition, a ligand and a stabilizer are added in sequence during the preparation of yttrium oxide sol. The ligand forms a coordination compound with yttrium ions in yttrium nitrate to prevent unnecessary redox reactions or other reactions that are not conducive to subsequent preparation in the solution. The stabilizer ensures the stability of the sol and avoids agglomeration or precipitation of sol particles. By setting the pH value of the mixed solution to 7-8, the surface of the particles of yttrium oxide sol carries an appropriate amount of charge, which helps the sol particles to better adhere to the surface of the quartz fiber during the subsequent impregnation process, thereby improving the impregnation effect. The entire yttrium oxide sol preparation process is simple, short in time, low in equipment consumption, and low in cost. The prepared yttrium oxide sol has good stability, excellent performance, and is easy to store, which is conducive to industrial production.
[0023] (2) The present invention uses citric acid monohydrate as a complexing agent, polyethylene glycol-400, urea or triethanolamine as a stabilizer, and ammonia water as a pH regulator. These three substances ensure that the product contains only yttrium oxide when preparing yttrium oxide sol, thereby ensuring the purity of the product; citric acid monohydrate and the stabilizer can be quickly oxidized and decomposed under low-temperature sintering conditions, and ammonia water is easy to volatilize during the reaction process. These three substances will not leave impurities and residues, have little effect on the dielectric properties of the wave-transmitting material, and will not introduce impurities in the subsequent impregnation process to affect the performance of the quartz fiber, thereby ensuring the quality and performance of the quartz fiber finally formed;
[0024] (3) The present invention limits the ratio of citric acid monohydrate to yttrium nitrate, and the ratio of stabilizer to yttrium nitrate. Since citric acid monohydrate mainly forms a coordination compound with yttrium nitrate, limiting the ratio of citric acid monohydrate to yttrium nitrate ensures the sufficiency of the coordination effect and avoids unnecessary precipitation or agglomeration of yttrium ions during the reaction. The stabilizer mainly prevents the agglomeration of the sol. Limiting the ratio of citric acid monohydrate to yttrium nitrate helps to make the particles in the sol more evenly dispersed in the solution, improve the uniformity and stability of the sol, and lay a foundation for the subsequent impregnation process. In addition, by strictly controlling the amount of citric acid monohydrate and stabilizer, it is possible to avoid excessive consumption of resources while ensuring their respective performances and save costs.
[0025] (4) The present invention also removes the organic impregnating agent from the surface of the quartz fiber before impregnating it. The presence of the organic impregnating agent will affect the interfacial bonding force between the quartz fiber and the yttrium oxide sol, thereby reducing the final performance. The organic impregnating agent is removed by thermal sintering treatment, which has a fast removal efficiency and good effect. By strictly controlling the sintering temperature, heating rate and holding time, it can ensure that the organic impregnating agent is completely removed while avoiding excessive damage to the quartz fiber itself, thereby ensuring that the performance of the quartz fiber itself is not affected.
[0026] (5) The present invention strictly controls the impregnation time and drying temperature of the quartz fiber to ensure that the quartz fiber can be fully and evenly mixed with the yttrium oxide sol, so that the yttrium oxide sol particles can better adhere to the surface of the quartz fiber, thereby improving the impregnation effect; strictly controls parameters such as the sintering temperature, heating rate, and insulation time, so that the yttrium oxide sol coating can stably adhere to the surface of the quartz fiber, and ensures the stability of the sintering process, avoiding coating cracking or fiber damage caused by sudden temperature changes, and ultimately achieving improved strength and heat resistance of the quartz fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of the process of the present invention;
[0028] Figure 2 Schematic diagram of SEM characterization of the port and surface of a quartz fiber with yttrium oxide coating after high temperature treatment at 800°C and the port and surface of a quartz fiber without yttrium oxide coating after high temperature treatment at 800°C;
[0029] Figure 3 Schematic diagram of SEM characterization of the surface of quartz fiber with yttrium oxide coating before and after the organic wetting agent on the surface of quartz fiber is removed. DETAILED DESCRIPTION
[0030] The present invention is further described below in conjunction with specific embodiments and drawings.
[0031] like Figure 1 As shown, a method for preparing a quartz fiber with an yttrium oxide coating comprises impregnating the quartz fiber with an yttrium oxide sol, and drying and sintering the impregnated quartz fiber to obtain a quartz fiber with an yttrium oxide coating on the surface; the preparation process of the yttrium oxide sol is as follows:
[0032] S1: Add a ligand and a stabilizer to an yttrium nitrate solution in sequence, stir and dissolve to form a mixed solution, add a pH adjuster to adjust the pH value of the mixed solution to 7-8, heat to a target temperature, and then cool to obtain an yttrium oxide sol.
[0033] In this embodiment, by forming an yttrium oxide coating on the surface of the quartz fiber, the high-temperature sintering resistance of the quartz fiber is greatly improved. At the same time, the yttrium oxide coating has strong oxidizability and ablation resistance under high temperature conditions, which protects the surface of the quartz fiber and thereby improves the mechanical properties of the quartz fiber at high temperatures.
[0034] At the same time, the present application creatively develops a preparation process of yttrium oxide sol, wherein a ligand and a stabilizer are sequentially added to an yttrium nitrate solution, and a coordination compound is formed between the ligand and the yttrium ions in the yttrium nitrate solution to stabilize the valence state of the yttrium ions, thereby preventing unnecessary redox reactions or other reactions that are not conducive to subsequent preparation in the solution; the stability of the sol is ensured by the stabilizer to avoid agglomeration or precipitation in the subsequent process; finally, the pH value of the mixed solution is adjusted to 7 to 8 by a pH regulator, within which range, yttrium nitrate can be gradually hydrolyzed and release yttrium ions, forming a stable coordination compound with the ligand, and then the sol is stabilized by the stabilizer, and finally a uniform and delicate yttrium oxide sol is formed. Finally, the particle surface of the yttrium oxide sol is made to have a uniform and appropriate charge, which helps the sol particles to better adhere to the surface of the quartz fiber, thereby ensuring the subsequent impregnation effect on the quartz fiber. The yttrium oxide sol preparation process is simple, short in time, low in equipment consumption, and low in cost. The prepared yttrium oxide sol has good stability, excellent performance, and is easy to store, which is conducive to industrial production.
[0035] It should also be noted that the existing mainstream method of improving the performance of quartz fiber at high temperatures is usually to directly introduce additives to improve the performance at the source of the quartz fiber, that is, during the preparation of the quartz fiber. However, the amount and type of additives added need to be strictly controlled, otherwise it may affect other properties of the quartz fiber, such as dielectric properties, etc.; and increase costs and time. Therefore, the present application directly impregnates the quartz fiber with yttrium oxide sol, so that an yttrium oxide coating is formed on the surface of the quartz fiber to improve the mechanical properties of the quartz fiber at high temperatures, which is efficient and effective.
[0036] In a specific embodiment, in step S1, the complexing agent is citric acid monohydrate, the stabilizer is one of polyethylene glycol-400, urea or triethanolamine, and the pH regulator is ammonia water.
[0037] Specifically, the specific substances used for the ligand, stabilizer and pH regulator are clearly defined in this embodiment. These three substances ensure that the product contains only yttrium oxide when preparing the yttrium oxide sol, thereby ensuring the purity of the product. Both citric acid monohydrate and the stabilizer can be rapidly oxidized and decomposed under low-temperature sintering conditions, and ammonia water is easy to volatilize during the reaction process. These three substances will not leave impurities and residues, and will not have much effect on the dielectric properties of the wave-transmitting material. At the same time, impurities will not be introduced during the subsequent impregnation process to affect the performance of the quartz fiber, thereby ensuring the quality and performance of the quartz fiber finally formed.
[0038] In a specific embodiment, the molar ratio of yttrium nitrate to citric acid monohydrate is 1:(1.0-2.0); the mass ratio of yttrium nitrate to stabilizer is (100-300):1.
[0039] Since citric acid monohydrate mainly forms a coordination compound with yttrium ions in the yttrium nitrate solution, in order to avoid unnecessary reactions in the solution, the molar ratio of citric acid monohydrate and yttrium nitrate is strictly limited, which can ensure that the coordination effect is fully carried out while avoiding unnecessary waste of resources; since the stabilizer mainly prevents the sol from agglomerating, the mass ratio of the stabilizer and yttrium nitrate is strictly limited, which ensures the stability of the sol during the preparation and storage process while avoiding the problem of increased costs caused by excessive waste of stabilizer dosage.
[0040] In a specific embodiment, the target temperature in step S1 is 50°C to 90°C, and the heating time is 30min to 90min. Appropriate heating temperature and heating time can accelerate the movement speed of molecules in the solution, promote the complexation reaction between the coordination agent and the yttrium ions and the formation process of the sol, and ensure that the formation process of the sol is neither too slow nor too intense, thereby avoiding waste of resources.
[0041] In a specific embodiment, the yttrium nitrate solution in step S1 is prepared by dissolving yttrium nitrate hexahydrate in water, and the concentration of the yttrium nitrate solution is 1.5 mol / L to 2.5 mol / L. Within this concentration range, yttrium nitrate hexahydrate can be well dissolved in water, easily forming a uniform and transparent solution, and can avoid the phenomenon of yttrium nitrate being oversaturated and precipitated, thereby ensuring the stability of the solution; at the same time, it can avoid the subsequent reaction efficiency being too fast and difficult to control due to too high a concentration; and the reaction rate being too slow due to too low a concentration, thereby affecting the production efficiency.
[0042] In a specific embodiment, before impregnating the quartz fiber with the yttrium oxide sol, the process also includes removing the organic impregnant on the surface of the quartz fiber to prevent the presence of the organic impregnant from affecting the interface bonding force between the quartz fiber and the yttrium oxide sol, thereby reducing the final performance.
[0043] Preferably, in this embodiment, the specific method of removing the organic impregnant on the surface of the quartz fiber is as follows: the quartz fiber is subjected to heat sintering in air to remove the organic impregnant on the surface, and the sintering temperature is 400°C to 600°C. The appropriate sintering temperature can ensure that the organic impregnant is completely removed, and the introduction of impurities is avoided to the greatest extent, while avoiding excessive damage to the quartz fiber itself. The heating rate is 5°C / min to 20°C / min, and the holding time is 60min to 240min. The appropriate heating rate and holding time can help control the uniformity and stability of the entire treatment process, and are easy to control and adjust.
[0044] In a specific embodiment, the quartz fiber is impregnated with the yttrium oxide sol for 30 minutes to 360 minutes, and the drying temperature is room temperature to 150°C for uniform heating and drying. In this embodiment, the impregnation time is a very important factor. Within this time range, it can ensure that the yttrium oxide sol can fully penetrate into the internal structure of the quartz fiber and form a dense and uniform yttrium oxide coating on the surface of the quartz fiber, thereby improving the overall performance of the quartz fiber. Uniform and slow drying can help the solvent in the sol to gradually volatilize, forming a stable coating, and preparing for the subsequent sintering process.
[0045] In a specific embodiment, the sintering temperature of the quartz fiber after impregnation is 200°C to 800°C. Maintaining the sintering temperature within this range helps to eliminate voids and defects in the yttrium oxide coating and improve the density and uniformity of the yttrium oxide coating; and ensures that the yttrium oxide coating can be tightly bonded to the quartz fiber; the heating rate is 5°C / min to 20°C / min, which ensures a smooth temperature change during the sintering process and avoids coating cracking or fiber damage caused by too rapid temperature changes; the insulation time is 30min to 240min, which helps to eliminate the residual stress generated during the sintering process and improve the overall stability and durability of the composite material.
[0046] Specifically, a quartz fiber with yttrium oxide coating is prepared by the preparation method of a quartz fiber with yttrium oxide coating as described above. The melting point of yttrium oxide is 2410℃, and it has extremely high temperature resistance, and can withstand the effects of extreme environments such as high-temperature oxidation, reduction and melting erosion. At high temperatures, yttrium oxide can still maintain its chemical and physical properties stable without any changes. The yttrium oxide sol prepared with yttrium oxide as the initial raw material is an inorganic coating with adhesiveness, which can be applied to the surface of special fiber materials, and has the advantages of improving material hardness, enhancing strength, inhibiting chemical reactions on the contact surface between two phases, high temperature resistance, oxidation resistance, and corrosion resistance. Therefore, the inventor of the present application creatively uses yttrium oxide sol to treat the surface of quartz fiber, which can greatly improve the high-temperature sintering performance of quartz fiber. At the same time, the yttrium oxide coating has strong oxidation resistance and ablation resistance under high temperature conditions, and protects the surface of quartz fiber, thereby improving the mechanical properties of quartz fiber at high temperatures, and finally achieving the purpose of improving the adaptability and wide application of quartz fiber as a reinforcement.
[0047] In order to further facilitate the understanding of this application, the following examples are given:
[0048] Example 1
[0049] A method for preparing quartz fiber with yttrium oxide coating comprises the following steps:
[0050] S1: Weigh 1000g of water and add it to a three-necked flask, slowly add 689.4g of yttrium nitrate hexahydrate until it is dissolved by stirring, and prepare a 1.8mol / L yttrium nitrate solution, weigh 630g of citric acid monohydrate and 3.83g of urea in turn, add them to the yttrium nitrate solution and stir to dissolve, wherein the molar ratio of yttrium nitrate: citric acid monohydrate is 1:1.67, and the mass ratio of yttrium nitrate: urea is 180:1. Note that during the stirring process, use a water bath to cool and keep the temperature constant; after the complexing agent and stabilizer are completely dissolved, add concentrated ammonia water dropwise while stirring, adjust the pH of the mixed solution to 7.1, increase the reaction temperature to 80°C and keep the reaction warm for 40min, use a condenser to cool and reflux during the process to ensure that the mixed solution does not gel due to water evaporation, and after the reaction is completed, cool down to obtain yttrium oxide sol, which will not gel when placed at room temperature for more than 6 months;
[0051] S2: The quartz fiber is heated to 500°C at a rate of 15°C / min and sintered for 90 minutes to remove the surface wetting agent, and then immersed in the yttrium oxide sol prepared in S1 for 90 minutes. After being taken out, the temperature is gradually increased from room temperature to 80°C for drying, and finally the temperature is increased to 500°C at a rate of 10°C / min and sintered for 120 minutes to obtain a quartz fiber with a surface covered with yttrium oxide coating.
[0052] The prepared yttrium oxide coated quartz fiber and the quartz fiber without surface impregnation agent were sintered at 800℃. Before high temperature treatment, the tensile strength of the coated quartz fiber was 1.22±0.33MPa and the tensile modulus was 126.28±9.68MPa, which were comparable to the tensile strength (1.19±0.33MPa) and tensile modulus (123.40±17.14MPa) of the uncoated quartz fiber. After high temperature treatment, the tensile strength of the coated fiber is still 1.16±0.28MPa, the tensile modulus of the single fiber is 109.35±26.94Mpa, and the strength retention rate is 95.1%. After the quartz fiber without yttrium oxide coating is treated at 800℃, the tensile strength of the single fiber is reduced to 0.92±0.22MPa, the tensile modulus of the single fiber is 96.87±20.45Mpa, and the strength retention rate is only 77.3%, which is significantly reduced. It can also be clearly seen from the SEM image after high temperature treatment that after high temperature treatment, the surface of the quartz fiber with yttrium oxide coating ( Figure 2 a) and fracture ( Figure 2 b) No high-temperature ablation morphology was observed, but after high-temperature treatment in air, the quartz fiber without yttrium oxide coating showed obvious ablation and melting on the fiber surface ( Figure 2 c), and there are obvious ablation holes on the fracture surface ( Figure 2 d), which shows that the yttrium oxide coating can significantly improve the high temperature oxidation resistance, corrosion resistance and high temperature mechanical properties of quartz fiber.
[0053] Example 2
[0054] A method for preparing quartz fiber with yttrium oxide coating comprises the following steps:
[0055] S1: Weigh 1000g of water and add it to a three-necked flask, slowly add 612.8g of yttrium nitrate hexahydrate until it is dissolved by stirring, and prepare a 1.6mol / L yttrium nitrate solution. Weigh 525g of citric acid monohydrate and 3.83g of polyethylene glycol-400 in turn and add them to the yttrium nitrate solution and stir to dissolve, wherein the molar ratio of yttrium nitrate: citric acid monohydrate is 1:1.56, and the mass ratio of yttrium nitrate: polyethylene glycol-400 is 160:1. Note that during the stirring process, use a water bath to cool and keep the temperature constant. After the complexing agent and stabilizer are completely dissolved, add concentrated ammonia water dropwise while stirring, adjust the pH of the mixed solution to 7.5, increase the reaction temperature to 70℃ and keep the reaction warm for 50 minutes. During the process, use a condenser to cool and reflux to ensure that the mixed solution does not gel due to water evaporation. After the reaction is completed, cool down to obtain yttrium oxide sol;
[0056] S2: The quartz fiber is heated to 450°C at a rate of 10°C / min and sintered for 120 minutes to remove the surface wetting agent, and then immersed in the yttrium oxide sol prepared in S1 for 120 minutes. After being taken out, the temperature is gradually increased from room temperature to 90°C for drying, and finally the temperature is increased to 450°C at a rate of 10°C / min and sintered for 90 minutes to obtain a quartz fiber with a surface covered with yttrium oxide coating.
[0057] Example 3
[0058] A method for preparing quartz fiber with yttrium oxide coating comprises the following steps:
[0059] S1: Weigh 1000g of water and add it to a three-necked flask, slowly add 842.6g of yttrium nitrate hexahydrate until it is dissolved by stirring, and prepare a 2.2mol / L yttrium nitrate solution. Weigh 646.8g of citric acid monohydrate and 4.68g of urea in turn and add them to the yttrium nitrate solution and stir to dissolve, wherein the molar ratio of yttrium nitrate: citric acid monohydrate is 1:1.4, and the mass ratio of yttrium nitrate: urea is 180:1. Note that during the stirring process, use a water bath to cool and keep the temperature constant. After the complexing agent and stabilizer are completely dissolved, add concentrated ammonia water dropwise while stirring, adjust the pH of the mixed solution to 7.2, increase the reaction temperature to 60℃ and keep the reaction warm for 60min. During the process, use a condenser to cool and reflux to ensure that the mixed solution does not gel due to water evaporation. After the reaction is completed, cool down to obtain yttrium oxide sol;
[0060] S2: The quartz fiber is heated to 480°C at a heating rate of 12°C / min and sintered for 100 minutes to remove the surface wetting agent, and then immersed in the yttrium oxide sol prepared in S1 for 120 minutes. After being taken out, the temperature is gradually increased from room temperature to 100°C for drying, and finally the temperature is increased to 400°C at a heating rate of 10°C / min and sintered for 100 minutes to obtain a quartz fiber with a surface covered with yttrium oxide coating.
[0061] Example 4
[0062] A method for preparing quartz fiber with yttrium oxide coating comprises the following steps:
[0063] S1: Weigh 1200g of water and add it to a three-necked flask, slowly add 873.2g of yttrium nitrate hexahydrate until it is dissolved by stirring, and prepare a 1.9mol / L yttrium nitrate solution. Weigh 742.1g of citric acid monohydrate and 3.97g of triethanolamine in turn and add them to the yttrium nitrate solution and stir to dissolve, wherein the molar ratio of yttrium nitrate: citric acid monohydrate is 1:1.55, and the mass ratio of yttrium nitrate: triethanolamine is 220:1. Note that during the stirring process, use a water bath to cool and keep the temperature constant. After the complexing agent and stabilizer are completely dissolved, add concentrated ammonia water dropwise while stirring, adjust the pH of the mixed solution to 7.6, increase the reaction temperature to 75℃ and keep the reaction warm for 45 minutes. During the process, use a condenser to cool and reflux to ensure that the mixed solution does not gel due to water evaporation. After the reaction is completed, cool down to obtain yttrium oxide sol;
[0064] S2: The quartz fiber is heated to 550°C at a rate of 15°C / min and sintered for 60 minutes to remove the surface wetting agent, and then immersed in the yttrium oxide sol prepared in S1 for 150 minutes. After being taken out, the temperature is gradually increased from room temperature to 85°C for drying, and finally the temperature is increased to 300°C at a rate of 10°C / min and sintered for 150 minutes to obtain a quartz fiber with a surface covered with yttrium oxide coating.
[0065] Comparative Example 1
[0066] The difference between Comparative Example 1 and Example 1 is that the additive for adjusting the pH value of the mixed solution in step S1 is a sodium hydroxide aqueous solution, and the other operation steps are the same. During the experiment, it was found that the quartz fiber was partially gelled after being immersed in the yttrium oxide sol for 90 minutes, and the quartz fibers were adhered together after being heated and dried. Compared with the yttrium oxide sol prepared by adjusting with ammonia water in Example 1, the yttrium oxide solvent adjusted with sodium hydroxide solution has poor stability and gels in a short time at room temperature. This shows that ammonia water acts together with the stabilizer urea in the preparation process of yttrium oxide sol, which improves the stability of the sol and is conducive to the long-term storage and industrial production of yttrium oxide sol.
[0067] Comparative Example 2
[0068] The difference between Comparative Example 2 and Example 1 is that the surface of the quartz fiber is not subjected to high temperature burning to remove the organic impregnation agent before the quartz fiber is impregnated, and the other operation steps are the same. Figure 3 As shown by Figure 3 It can be found that after the surface of the quartz fiber without removing the surface impregnant was impregnated with yttrium oxide sol, the impregnant would be oxidized and decomposed in the middle layer during the second high-temperature sintering treatment. However, due to the wrapping of the surface sol, the impregnant could not be completely decomposed to form droplets, so that the yttrium oxide coating was not formed. However, after sintering to remove the impregnant, the surface of the quartz fiber ( Figure 3 b) No droplet-shaped particle accumulation is formed, and a smooth yttrium oxide coating is formed. The main reason is that the surface wetting agent is oxidized and decomposed during the high-temperature sintering process, resulting in the quartz fiber failing to interact with the yttrium oxide sol to form a stable yttrium oxide protective coating. The surface of the quartz fiber after the wetting agent is removed contains silanol, and the presence of silanol is conducive to the deposition of the yttrium oxide sol to form an yttrium oxide coating.
[0069] The examples described in the present invention are merely descriptions of the preferred implementation modes of the present invention, and are not intended to limit the concept and scope of the present invention. Without departing from the design concept of the present invention, various modifications and improvements made to the technical solutions of the present invention by engineers and technicians in this field should all fall within the protection scope of the present invention.
Claims
1. A method for preparing quartz fiber with yttrium oxide coating, characterized in that: The quartz fiber is impregnated with yttrium oxide sol, and the impregnated quartz fiber is dried and sintered to obtain a quartz fiber with a yttrium oxide coating on the surface; the preparation process of the yttrium oxide sol is as follows: S1: Add a ligand and a stabilizer to an yttrium nitrate solution in sequence, stir and dissolve to form a mixed solution, add a pH adjuster to adjust the pH value of the mixed solution to 7-8, heat to a target temperature, and then cool to obtain an yttrium oxide sol.
2. The method for preparing a quartz fiber with an yttrium oxide coating according to claim 1, characterized in that: In step S1, the complexing agent is citric acid monohydrate, the stabilizer is one of polyethylene glycol-400, urea or triethanolamine, and the pH regulator is ammonia water.
3. The method for preparing a quartz fiber with an yttrium oxide coating according to claim 2, characterized in that: The molar ratio of yttrium nitrate to citric acid monohydrate is 1:(1.0-2.0); the mass ratio of yttrium nitrate to stabilizer is (100-300):
1.
4. The method for preparing a quartz fiber with an yttrium oxide coating according to claim 1 or 2, characterized in that: In step S1, the target temperature is 50°C to 90°C, and the heating time is 30min to 90min.
5. The method for preparing a quartz fiber with an yttrium oxide coating according to claim 1, characterized in that: In step S1, the yttrium nitrate solution is prepared by dissolving yttrium nitrate hexahydrate in water, and the concentration of the yttrium nitrate solution is 1.5 mol / L to 2.5 mol / L.
6. The method for preparing a quartz fiber with an yttrium oxide coating according to claim 1, characterized in that: Before impregnating the quartz fiber with the yttrium oxide sol, the method further includes removing the organic impregnant on the surface of the quartz fiber.
7. The method for preparing a quartz fiber with an yttrium oxide coating according to claim 6, characterized in that: The specific method of removing the organic impregnant on the surface of the quartz fiber is as follows: the quartz fiber is subjected to a heat sintering treatment in air to remove the organic impregnant on the surface, the sintering temperature is 400°C to 600°C, the heating rate is 5°C / min to 20°C / min, and the insulation time is 60min to 240min.
8. The method for preparing a quartz fiber with an yttrium oxide coating according to claim 1 or 6, characterized in that: The time for impregnating the quartz fiber with the yttrium oxide sol is 30 minutes to 360 minutes, and the drying temperature is room temperature to 150° C. for uniform heating and drying.
9. The method for preparing a quartz fiber with an yttrium oxide coating according to claim 1, characterized in that: The sintering temperature of the quartz fiber after impregnation is 200°C to 800°C, the heating rate is 5°C / min to 20°C / min, and the insulation time is 30min to 240min.
10. A quartz fiber with an yttrium oxide coating, characterized in that: The quartz fiber is prepared by the method for preparing a quartz fiber with an yttrium oxide coating as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Surface modification method for quartz fibre
CN102249557B
Preparation method of modified quartz fiber and application of modified quartz fiber in composite material
CN118909308A
Cited By
Quartz glass fiber cloth and preparation method thereof
CN120818934A